Lingkungan dan Disiplin Kerja Memoderasi Pengaruh Kompetensi Terhadap Kinerja Auditor - Utami, N. Diah; Dwirandra, A. A.Ngurah Bagus (E-Jurnal Akuntansi, 2018)
Environment and job discipline can influence the competence of auditor's performance in carrying out audit examination. Competence will improve the performance of auditors if the surrounding environment is able to support in carrying out its duties. Likewise with the discipline able to improve the competence that will affect the performance auditornya. This research is intended to know the moderation of environment and job discipline on auditor competence. This research was conducted at Inspectorate Office of Denpasar City. The number of respondents used as many as 40 auditors selected using purposive sampling technique with the criteria of respondents namely the Office of Inspectorate of Denpasar who are willing to accept the questionnaire and become respondents. Methods of data collection were conducted by survey method using questionnaire. Data analysis technique used is Moderated Regresion Analysis (MRA). The result of the research stated that the competence variable has an effect on the performance of the auditor, the job environment variables to moderate the influence of competence on the auditor's performance, the job discipline variable can moderate the influence of competence on the auditor's performance. Keywords: influence of competence, job environment, job discipline, auditor performance